Moles: tool-assisted environment isolation with closures - Halleux, Jonathan "Peli" de; Tillmann, Nikolai (TOOLS'10, 2010)
Isolating test cases from environment dependencies is often desirable, as it increases test reliability and reduces test execution time. However, code that calls non-virtual methods or consumes sealed classes is often impossible to test in isolation. Moles is a new lightweight framework which addresses this problem. For any .NET method, Moles allows test-code to provide alternative implementations, given as .NET delegates, for which C# provides very concise syntax while capturing local variables in a closure object. Using code instrumentation, the Moles framework will redirect calls to provided delegates instead of the original methods. The Moles framework is designed to work together with the dynamic symbolic execution tool Pex to enable automated test generation. In a case study, testing code programmed against the Microsoft SharePoint Foundation API, we achieved full code coverage while running tests in isolation without an actual SharePoint server. The Moles framework integrates with .NET and Visual Studio.